دراسة العلاقة بين الرجفان الأذيني و توسع الأذينة اليسرى - شيخ ابراهيم, عبد الله; جحجاح, أكرم; كفى, مصطفى (Latakia University Journal -Medical Sciences Series, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"جدول عادي"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> قمنا في مشفى الأسد الجامعي باللاذقية وخلال الفترة الممتدة من شباط 2012وحتى شباط 2013 بدراسة عينة عشوائية مكونة من 97 مريضاً (ذكوراً و إناثاً) موزعين على ثلاث مجموعات: المجموعة الأولى وتضم 16 مريضاً لديهم توسع أذينة يسرى بدون رجفان أذيني ،المجموعة الثانية و تضم 70 مريضاً لديهم توسع أذينة يسرى مع رجفان أذيني ،المجموعة الثالثة وتضم 11مريضاً لديهم رجفان أذيني بدون توسع أذينة يسرى. تم في هذه الدراسة قياس مشعر حجم الأذينة اليسرى (LAVI) باستخدام الايكو دوبلر القلبي من خلال طريقة سيمبسون، وذلك لتقييم علاقته بحدوث الرجفان الأذيني.حيث وجد في هذه الدراسة أن ثلاثة مرضى من المجموعة الأولى (16مريضاً) أي ما يقارب حوالي 18.75% تطور لديهم رجفان أذيني بعد سنة من المتابعة أي أن توسع الأذينة اليسرى يخدم كمتنبئ لحدوث الرجفان الأذيني.كما لوحظ أيضا استمرار الرجفان الأذيني و ديمومته مع حدوث زيادة في حجم الأذينة اليسرى بعد مرور سنة من متابعة مرضى المجموعة الثانية. بالمقابل فإن خمسة مرضى من المجموعة الثالثة ( 11 مريضاً) حدث لديهم زيادة في مشعر حجم الأذينة اليسرى في نهاية فترة الدراسة أي بنسبة قدرها45.45 % (P<0.001) ، وعليه فإن الرجفان الأذيني يمكن أن يسبب توسع أذينة يسرى. وعلى الرغم من أن توسع الأذينة اليسرى يمكن أن يسبب رجفاناً أذينياً، والعكس بالعكس حسب ما توصلنا إليه وفق نتائج بحثنا ، فإن هذه الدراسة أظهرت أيضاً احتمال وجود عوامل أخرى مؤهبة تلعب دوراً في حدوث ونشوء الرجفان الأذيني. A study was conducted in Al-Assad University Hospital in Lattakia during the period February 2012 and February 2013. The study included a random sample of 97 patients (males and females) divided into three groups: the first group consisted of 16 patients with left atrial enlargement with no atrial fibrillation, the second group included 70 patients who had left atrial enlargement with atrial fibrillation, and the third group of 11 patients had atrial fibrillation with no left atrial enlargement. In the study, the ECHO Doppler was used for measuring left atrial volume index (LAVI) through the Simpson method. This is in order to assess the role and relationship with the occurrence of atrial fibrillation. It was found out that three patients out of 16 fromthe first group (about 18.75%) developed an atrial fibrillation after one year of follow-up, which means that the left atrial enlargement gave a predication of the occurrence of atrial fibrillation. The continuation of atrial fibrillation was also noticed together with its lifetime with an increase in the size ofleft atrial after one year of following-up the patients of the second group. 3 out of 11 patients fromthe third group had an increase in the left atrial volume index at the end of the study i.e. 45.45%.Accordingly, the atrial fibrillation could cause left atrial enlargement.Even though the left atrial enlargement may cause atrial fibrillation, and vice versa, according to thisstudy, the study shows the possibilities of existence of other variable factors related to atrial fibrillation whichplay a role in the occurrence.